Perspectives of rural development problems and prospects - Basu Arabinda; Das Rajat Kanti; Guha Abhijit (Kolkata Indian Anthropological Society, 2006)
This book is an outcome of the Annual Conference of the Indian Anthropological Society held at Vidyasagar University which focuses the rural development became a familiar subject in the academic arena. It lies in providing theoretical and empirical treatm
Keywords: Rural development